2000
DOI: 10.1038/labinvest.3780125
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Rat Mesentery Vasculature in Experimental Diabetes

Abstract: SUMMARY:The alteration induced by diabetes on vascular permeability to serum albumin was investigated in the mesentery of streptozotocin-induced hyperglycemic rats. Double-tagged ( 125 I and dinitrophenol-haptenated) heterologous albumin was intravenously administered in normal and hyperglycemic animals, and the extravasation of the tracer was evaluated by radioactivity measurements and by morphometry at the ultrastructural level using quantitative protein A-colloidal gold immunocytochemistry. The results demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 70 publications
(86 reference statements)
3
18
0
Order By: Relevance
“…Similar increases in the total number of plasmalemmal vesicles was reported in endothelial cells of STZinjected animals at the level of the muscle capillaries [49]. Also a similar increase in albumin transport by endothelial cells was reported in mesenteric capillaries of hyperglycaemic animals [41]. The low number of the plasmalemmal vesicles in the CNS endothelial cells has been well established and is considered as one of the features responsible for the low permeability to macromolecules attributed to the blood-brain barrier [1,5,6,8,43].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Similar increases in the total number of plasmalemmal vesicles was reported in endothelial cells of STZinjected animals at the level of the muscle capillaries [49]. Also a similar increase in albumin transport by endothelial cells was reported in mesenteric capillaries of hyperglycaemic animals [41]. The low number of the plasmalemmal vesicles in the CNS endothelial cells has been well established and is considered as one of the features responsible for the low permeability to macromolecules attributed to the blood-brain barrier [1,5,6,8,43].…”
Section: Discussionsupporting
confidence: 65%
“…The passage of this protein across the capillary wall was comparatively evaluated on brain frontal lobe tissues from age-matched normoglycaemic and STZ-injected rats at two intervals after the onset of the hyperglycaemic state. The relation between the density of the immunolabelling and the actual concentration of the detected tracer has been well established [41,42]. Changes in albumin permeability were found in normoglycaemic rats along with their age as well as between normo-glycaemic and hyperglycaemic rats.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, this model was used in the first study of the effects of nitric oxide (NO) on lymph microvessels in vivo: Shirasawa et al [35] showed the influence of a NO synthase inhibitor on lymphatic diameter and contractile activity, which was reversed after applying an endogenous NO donor (L-arginine). This model has also been employed to study microcirculation disturbances in experimental models of diseases such as diabetes, ischemia, hemorrhage, shock, inflammation, tumor, edema, and others [2,4,13,21,22,36,37] . Recent discoveries in cell biology (e.g., identification of the genes, such as VEGF-C and VEGF-D, expressed by endothelium or endothelial g rowth factors for lymphatics), along with advances in optical techniques (e.g., lasers, high-speed digital cameras, powerful software) have increased interest in this model and its capabilities for studying the fundamentals of blood and lymph microcirculation, including its potential for the molecular imaging of individual cells in vivo [38][39][40] .…”
Section: Introductionmentioning
confidence: 99%